Experimental study of CO2 adsorption on various functional adsorbents - Tan, Boon Chiong (Nanyang Technological University, 2020)
Global warming has been a worldwide concern in the recent years, as human continues to burn fossil fuel for energy. This is the result of high emission of greenhouse gases, especially CO2. As the increases of the CO2 emission, more methods of 5CO2 capture technologies are required to be investigate and work on it. Therefore, methods like post-combustion, oxyfuel and pre-combustion are commonly used for the CO2 capture technologies. For the experimental purpose, we focus mostly on the post-combustion. The post-combustion is split into two different part of the capture technologies mainly the chemical and physical absorption. In this report, the CO2 adsorption on various porous materials such as metal organic frameworks (MOFs), zeolite and their composites are studied. The CO2 uptakes are measured at 298 K and pressures ranging from 1 bar to 7 bar. Hence the volumetric methodology is employed. The surface characteristics of these functional adsorbents are also evaluated by scanning electron micrography (SEM) and N2 adsorption analysis. Various isotherms and kinetics models are studied in this report with uncertainty analysis. Both volumetric and gravimetric uptakes are measured under low pressure conditions. It is found that MOFs are promising for CO2 storage under ambient temperature and low-pressure conditions. However, a detailed analysis is required.